Clinical practice guideline for diagnosis and management of urticaria - Kanokvalai Kulthanan (2018)
© 2016, Allergy and Immunology Society of Thailand. All rights reserved. Urticaria is a common skin condition that can compromise quality of life and may affect individual performance at work or school. Remission is common in majority of patients with acute spontaneous urticaria (ASU); however, in chronic cases, less than 50% had remission. Angioedema either alone or with urticaria is associated with a much lower remission rate. Proper investigation and treatment is thus required. This guideline, a joint development of the Dermatological Society of Thailand, the Allergy, Asthma, and Immunology Association of Thailand and the Pediatric Dermatological Society of Thailand, is graded and recommended based on published evidence and expert opinion. With simple algorithms, it is aimed to help guiding both adult and pediatric physicians to better managing patients who have urticaria with/without angioedema. Like other recent guideline, urticaria is classified into spontaneous versus inducible types. Patients present with angioedema or angioedema alone, drug association should be excluded, acetyl esterase inhibitors (ACEIs) and non-steroidal anti-inflammatory drugs (NSAIDs) in particular. Routine laboratory investigation is not cost-effective in chronic spontaneous urticaria (CSU), unless patients have clinical suggesting autoimmune diseases. Non-sedating H1-antihistamine is the first-line treatment for 2-4 weeks; if urticaria was not controlled, increasing the dose up to 4 times is recommended. Sedating first-generation antihistamines have not been proven more advantage than non-sedating antihistamines. The only strong evidence-based alternative regimen for CSU is an anti-IgE: omalizumab; due to very high cost it however might not be accessible in low-middle income countries. Non-pharmacotherapeutic means to minimize hyper-responsive skin are also important and recommended, such as prevention skin from drying, avoidance of hot shower, scrubbing, and excessive sun exposure.